Prevalence and Risk Factors of Burnout Among Medical Residents in Tunisia: A Cross-Sectional Study - W. Haouari; S. Omri; A. Labyadh; I. Gassara; R. Feki; N. Charfi; J. Ben Thabet; M. B. Maalej; N. Smaoui; L. Zouari; M. Maalej (European Psychiatry, 2024)
Introduction The burnout syndrome is a blend of physical exhaustion and emotional fatigue that impairs an individual’s performance at work. In Tunisia, factors like working hours, the frequency of monthly shifts, and the physical and emotional abuse that physicians face from patients have collectively led to a significant incidence of burnout among medical professionals.